2016
DOI: 10.4314/gjedr.v15i1.6
|View full text |Cite
|
Sign up to set email alerts
|

School absenteeism among primary school pupils in cross river state: psychological implication for national development

Abstract: Handling of issues and challenges in education at the primary school level believed to be the foundation on which other levels of education rest on will either promote or mar the onward movement of individuals to the other levels of education and the achievement of the objective of education as an instrument for national development. It is against this background that this study attempted to examine the causes of school absenteeism among primary school pupils in the three senatorial zones of Cross River State … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Ill health is one of the very common reasons for absenteeism in Primary schools in Nigeria [29] and our findings corroborated this statement. The average duration of hospital stay was 22.94±13.56 days, which is 22 days spent away from school.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Ill health is one of the very common reasons for absenteeism in Primary schools in Nigeria [29] and our findings corroborated this statement. The average duration of hospital stay was 22.94±13.56 days, which is 22 days spent away from school.…”
Section: Discussionsupporting
confidence: 87%
“…The average duration of hospital stay was 22.94±13.56 days, which is 22 days spent away from school. If regular school attendance is a pre-requisite for acquiring skills and knowledge for good academic success, [29] it then follows that this long duration of hospital stay will impact negatively on the academic achievements of these children. Other studies in Nigeria showed similar duration of hospital stay [8,14,16].…”
Section: Discussionmentioning
confidence: 99%
“…Those students who sustained an illness had more risk of being absent from the school compared with their counterparts. Studies from Nigeria and Ghana also investigated that illness is one of the top factors affecting school absenteeism [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stress management, according to Amalu and Bekomson (2022), is a combination of approaches, activities, and treatments aimed to help people cope with stress better by assessing particular sources of stress and implementing constructive behaviors to lessen their impact. Effective management will assist teachers in breaking the grip that stress has on their lives, allowing them to be more cheerful and more fulfilled.…”
Section: 2stress Management Strategiesmentioning
confidence: 99%